2020
DOI: 10.3389/fmicb.2020.01213
|View full text |Cite
|
Sign up to set email alerts
|

Amoxicillin Increased Functional Pathway Genes and Beta-Lactam Resistance Genes by Pathogens Bloomed in Intestinal Microbiota Using a Simulator of the Human Intestinal Microbial Ecosystem

Abstract: Liu et al. AMX Influences Intestinal Microbiota in SHIME gene numbers (R = 0.98, P < 0.001) or bl2_len and bl2be_shv2 abundance (R = 0.94, P < 0.001); (iii) the changes caused by AMX were "SHIME-compartment" different with more significant alteration in ascending colon, and the effects were permanent, which could not be restored after 2-week AMX discontinuance. Overall results demonstrated negative side-effects of AMX, which should be considered for AMX prescription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 77 publications
4
22
1
1
Order By: Relevance
“…Our previous in vitro studies also discovered this phenomenon [36,37]. At the genus level, it has been veri ed in our previous study that after Amx exposure, Bacteroides and Klebsiella were enriched in the intestinal ora, while the abundance of Bi dobacterium was reduced [37]. These data related to Amx effects can also be supported by early reports [22,38,39].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Our previous in vitro studies also discovered this phenomenon [36,37]. At the genus level, it has been veri ed in our previous study that after Amx exposure, Bacteroides and Klebsiella were enriched in the intestinal ora, while the abundance of Bi dobacterium was reduced [37]. These data related to Amx effects can also be supported by early reports [22,38,39].…”
Section: Discussionsupporting
confidence: 71%
“…For in vivo studies, highest percentage of Proteobacteria had also been observed in fecal samples from healthy human and animals [34,35]. Our previous in vitro studies also discovered this phenomenon [36,37]. At the genus level, it has been veri ed in our previous study that after Amx exposure, Bacteroides and Klebsiella were enriched in the intestinal ora, while the abundance of Bi dobacterium was reduced [37].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The effects of antibiotics on alpha diversity, the taxon richness (Chao1 index), evenness (Simpson index), and diversity (Shannon index) were calculated for all the samples as previous did [91,92]. Linear discriminant analysis effect size (LEfSe) was performed to determine bacterial taxa that were signi cantly differed between the six groups using the Galaxy application tool [93].…”
Section: S Rrna Gene Sequencing and Analysismentioning
confidence: 99%
“…High-throughput-qPCR reactions were performed using the Wafergen SmartChip Real-time PCR system as previous did [91,92]. The reactions were conducted by Anhui MicroAnaly Gene Technologies Co., Ltd (Anhui, China).…”
Section: High-throughput Quantitative Pcr (Ht-qpcr) and Analysismentioning
confidence: 99%